Identification, characteristics and rice growth promotion of a highly efficient cellulolytic bacterial strain, Cellulomonas iranensis ZJW-6, isolated from paddy soil in central China - Wu, Lei; Che, Songhao; Qin, Xueting; Xu, Yufeng; Tian, Shiqi; Zhu, Yuan; Song, Jian; Guan, Yunpeng; Wang, Dongchao; Wu, Meikang; Yang, Xue; Wu, Zhihai; et al. (Frontiers in Microbiology, 2023)
To explore and utilize the microbial resources of lignocellulose degradation, 27 lignocellulose degrading strains were screened from 13 regions in China. ZJW-6 was concerned because of its 49.6% lignocellulose weight loss rate. According to the theoretical analysis of the experimental results, the following straw degradation conditions were obtained by ZJW-6: nitrogen source input of 8.45 g/l, a pH of 8.57, and a temperature of 31.63 °C, the maximum weight loss rate of rice straw could reach 54.8%. It was concluded that ZJW-6 belonged to Cellulomonas iranensis according to 16s rRNA gene sequence comparison and identification. ZJW-6 is a Gram-positive bacterium that grows slowly and has a small yellowish green colony. To explain the degradation mechanism of lignocellulose, the experiment of enzymatic properties of the strain was prepared and carried out. It was discovered that ZJW-6 has an excellent ability to degrade cellulose, hemicellulose, and lignin, with cellulose and hemicellulose loss rates reaching almost 50% in 4 days and lignin loss rates reaching nearly 30%. Furthermore, ZJW-6 demonstrated lignocellulose degradation under aerobic and anaerobic conditions, indicating the strain's broad application potential. ZJW-6 was found to be more effective than ordinary humic acid in improving rice soil (available phosphorus, available nitrogen, organic matter) and promoting rice growth in a rice pot experiment (increasing root-shoot ratio, root activity, chlorophyll content and net photosynthetic rate). ZJW-6 plays an important role in promoting the development and utilization of straw resources. It has important significance for the advancement of green agriculture.